Combating unlawful acts against the safety of maritime navigation under the sua convention - Ansari, Abdul Haseeb; Kyaw Hla Win @ Md. Hassan Ahmed, Hassan; Hamid, Abdul Ghafur@Khin Maung Sein (The Indian Society of International Law, 2014)
Prior to the Achille Lauro incident, there was a lack of a compressive legal framework for taking appropriate action against unlawful acts endangering the safety of maritime navigation at both the international and regional levels. Thus, the incident was not an attack, which falls within the ambit of the definition of piracy under the United Nations Convention on the Law of the Sea 1982 as the attack was originated from the target ship itself for political gain within the Egyptian jurisdiction. This State of affairs induced the international community to create a comprehensive legal regime, which covers all possible acts and attacks, which may amount to maritime terrorism committed for political ends. Accordingly, the international community adopted the Convention for the Suppression of Unlawful Acts Against the Safety of Maritime Navigation 1988 under the auspices of the International Maritime Organization in order to address the increasing danger of maritime terrorism and it manages to attract quite a number of States to be Parties. Nonetheless, it seems less effective in combating piracy and suppressing maritime terrorism due to some deficiencies especially pertaining to enforcement measures, i.e., jurisdiction, extradition and prosecution. This paper analyses the said shortcomings without forgetting to propose viable solutions to those loopholes.